PENGARUH LIKUIDITAS, UKURAN PERUSAHAAN, RISIKO BISNIS DAN USIA PERUSAHAAN TERHADAP STRUKTUR MODAL PADA INDUSTRI PARIWISATA DI BURSA EFEK INDONESIA PERIODE 2010-2013 - Wardana, I Putu Arya Ditha; Sudiartha, Gede Mertha (E-Jurnal Manajemen, 2015)
The purpose of this study was to determine the effect of  liquidity, firm size, business risk and age to the capital structure of tourism industry. This research was conducted in the Indonesia Stock Exchange with the period 2010-2013. The method of determining the sample is purposive sampling with a sample of 15 companies enganged in the tourism industry. The analysis technique used in this study is the technique of multiple linear regression analysis. The findings indicate that liquidity, firm size and age of the company partially significant negative effect on the capital structure of the tourism industries in Indonesia Stock Exchange in 2010-2013, while the business risk has a significant positive effect on the capital structure of the tourism industry in Indonesia Stock Exchange from 2010-2013.
Keywords: capital structure, liquidity, firm size, business risk, age.